Factors associated with the cure for tuberculosis in Northern Minas Gerais, 2009 to 2018 (Research, Society and Development, 2021)
Objective: This study aims to analyze the factors associated with the cure of pulmonary Tuberculosis in the North of Minas Gerais/Brazil, from 2009 to 2018. Methods: Cross-sectional and analytical study, using data from notifications of patients residing in 53 municipalities registered in the years from 2009 to 2018 in the Information System for Compulsory Notifications (SINAN). The existence of associations between the variable status of closure (cure/non-cure) and sex, age, race, education, special populations, risk factors/comorbidities and programmatic assistance variables, proposed in a theoretical model of axes of vulnerabilities, were verified. For this purpose, Pearson's Chi-square test or Fisher's exact test were performed, for expected values less than five, and by binary logistic regression, odds ratio and 95% confidence intervals were calculated for all significant variables p